Dose Analysis in Boron Neutron-capture Cancer Therapy (BNCT) Neutron Generator Based for Breast Cancer - Rawi Pramusinta; R Zailani; Yohannes Sardjono (Indonesian Journal of Physics and Nuclear Applications, 2019)
The purpose of this study is to know the concentration of boron and irradiation times which optimizes the treatment of breast cancer using the BNCT method. This research was conducted by using MCNPX simulation which outputs are flux neutron, neutron scattering dose and gamma dose. The neutron source used is the BSA D-D Neutron generator model. The independent variable of this research is the boron concentration injected into the cancer. The dependent variable is the total dose rate and irradiation time which determines the effectiveness of BNCT therapy. The controlled variables are the output of the neutron flux, dose and gamma neutron scattering dose. The results showed that in the range of 70-150 µg/g, the dose rate received by cancer increases with increasing the concentration of boron-10. If the dose rate is increased, the irradiation time interval will be faster. The Boron dose of 70 μg/g and the dose rate of irradiation 0.00293603 Gy/sec needs an irradiation time of 409.43 minutes; the boron dose of 90 µg/g and the dose rate of irradiation 0.00241049 Gy/sec needs an irradiation time of 345.71 minutes; the boron dose of 110 µg/g and the dose rate of irradiation 0.00271236 Gy/sec needs an irradiation time of 307.24 minutes; the boron dose of 130 µg/g and the dose rate of irradiation 0.00303389 Gy/sec needs an irradiation time of 274.67 minutes; and the boron dose 150 µg/g and the dose rate of irradiation 0.00334565 Gy/sec needs an irradiation time of 249.08 minutes. The Optimum concentration of boron is 150 µg/g with irradiation time of 249.08 minutes.